The iconography of Inca Garcilaso de la Vega - González Umeres, Luz (Mercurio Peruano, 2016)
The painter Francisco González Gamarra produced a series of representations which were trying to show a mixed picture of the Innca Garcilaso and around such series he wrote some notes and observations which are preserved in the familiy archive of the artist in the city of Lima. In this work the material is ordered following the logic of those who work humanistic disciplines, offering some notes in chronological order around such consiederations. However, I leave for later the answering, as deserve, of the questions of aesthetic nature that have been dawning while trying to sort the data in question. Those are queries that want to go beyond the data and correspond to the aesthetics and anthropology.